2023
DOI: 10.2215/cjn.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Eosinophilic Aggregates and Kidney Outcome in Patients with CKD

Koki Hattori,
Yusuke Sakaguchi,
Tatsufumi Oka
et al.

Abstract: Background Interstitial eosinophilic aggregates are observed in various kidney diseases, but their clinical implications remain unknown. We assessed the association between interstitial eosinophilic aggregates and kidney outcomes and further analyzed the association between blood eosinophil count, as a surrogate for interstitial eosinophilic aggregates, and the risk of kidney failure in patients with advanced CKD. Methods We analyzed datasets from two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Coincidentally, a recent study confirmed the causal relationship between eosinophils and an increased risk of diabetic nephropathy using Mendelian randomization analysis [ 31 ]. These findings suggested that eosinophils in the blood may have a causal relationship with interstitial eosinophilic aggregates in renal tissue, potentially influencing the development and progression of CKD and even leading to ESKD, as indicated by two recent cohorts [ 6 ]. Furthermore, eosinophil fractions were found to be positively associated with glomerular basement membrane width and negatively associated with glomerular filtration surface density, which may contribute to albuminuria [ 32 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Coincidentally, a recent study confirmed the causal relationship between eosinophils and an increased risk of diabetic nephropathy using Mendelian randomization analysis [ 31 ]. These findings suggested that eosinophils in the blood may have a causal relationship with interstitial eosinophilic aggregates in renal tissue, potentially influencing the development and progression of CKD and even leading to ESKD, as indicated by two recent cohorts [ 6 ]. Furthermore, eosinophil fractions were found to be positively associated with glomerular basement membrane width and negatively associated with glomerular filtration surface density, which may contribute to albuminuria [ 32 ].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested a correlation between peripheral eosinophil counts (PEC) and CKD, encompassing disease incidence, progression, and prognosis [ 6–18 ] ( Table 1 ). It has been reported that patients with CKD exhibit higher PEC compared to non-CKD individuals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation